Rancang Bangun Penilaian Keaktifan Menggunakan Teknik Text Similarity Pada Sistem Tutorial Matematika Diskret - Astawa, I Gede Santi; Harini, Luh Putu Ida; Cahyaning, Putri (Jurnal Matematika, 2015)
Facility of student activeness in adaptif tutorial system expected be one of the supporting facilities. Activity of students in learning process is process that construct their own knowledge. They are actively building an understanding of the issues or anything they encounter in the learning process.  Because it is constructed from the inside, causing the activity is difficult to assess without having to do face to face, especially the tendency of students to be silent and conceal their ignorance will cause more difficult to assess the students' activity. In this study, the authors designed an extra feature on discrete mathematics tutorial system that has been built, in the form of an online discussion forum to help educators in scoring liveliness (seen from match students' comments and answer key). In this feature, the method used is the method of measuring similarity (similarity text) Rabin Karp to determine the similarity of the comments. Result of the research shows that the feature has been able to increase student interest in providing comments, which given an average of 2.2 comment in every single student. But rabin Karp algorithm used is still deemed less good if a comment is composed of words with errors in typing, necessitating the addition of other algorithms for increase system performance.
Keywords: Discussion Forum; text simmilarity; student activity